2022
DOI: 10.1038/s41429-022-00524-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel small-molecular inhibitors of Staphylococcus aureus sortase A using hybrid virtual screening

Abstract: Staphylococcus aureus is one of the most dangerous pathogens commonly associated with high levels of morbidity and mortality. Sortase A is considered as a promising molecular target for the development of antistaphylococcal agents. Using hybrid virtual screening approach and FRET analysis, we have identified five compounds able to decrease the activity of sortase A by more than 50% at the concentration of 200 µM. The most promising compound was 2-(2-amino-3-chloro-benzoylamino)-benzoic acid which wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…[12] Pharmacophore modeling and molecular docking followed by experimental study showed that 2-(2-amino-3-chlorobenzoylamino)benzoic acid exhibited IC 50 value of 59.7 μM for sortase A of S. aureus. [13] Rahman et al reported Lumacaftor, Dihydroergocornine, and Olaparib as potent molecules for S. aureus FemX. [15] Figure 8.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[12] Pharmacophore modeling and molecular docking followed by experimental study showed that 2-(2-amino-3-chlorobenzoylamino)benzoic acid exhibited IC 50 value of 59.7 μM for sortase A of S. aureus. [13] Rahman et al reported Lumacaftor, Dihydroergocornine, and Olaparib as potent molecules for S. aureus FemX. [15] Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…reported the molecules: PC‐124127620, PC‐124127795 and PC‐124127805) as potent candidate for dihydrofolate reductase of S. aureus [12] . Pharmacophore modeling and molecular docking followed by experimental study showed that 2‐(2‐amino‐3‐chlorobenzoylamino)‐benzoic acid exhibited IC 50 value of 59.7 μM for sortase A of S. aureus [13] . Rahman et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a clear and pressing need to develop new antimicrobial agents to fight these pathogens. A potential candidate for therapeutic development in Gram‐positive bacteria are inhibitors of sortase enzymes 7–12 …”
Section: Overviewmentioning
confidence: 99%